2016
DOI: 10.3102/0002831216652722
|View full text |Cite
|
Sign up to set email alerts
|

Income Segregation Between Schools and School Districts

Abstract: Although trends in the racial segregation of schools are well documented, less is known about trends in income segregation. We use multiple data sources to document trends in income segregation between schools and school districts. Between-district income segregation of families with children enrolled in public school increased by over 15% from 1990 to 2010. Within large districts, between-school segregation of students who are eligible and ineligible for free lunch increased by over 40% from 1991 to 2012. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
186
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(202 citation statements)
references
References 42 publications
4
186
0
3
Order By: Relevance
“…Recent research on the consequences of rising income inequality has focused on the economic segregation produced by more affluent residents sorting into different school districts than their less advantaged counterparts (Owens et al. ); these trends are particularly acute among parents (Owens ), which suggests that schooling considerations play a central role in parents’ residential choices. The growing economic segregation across school districts has contributed to rising inequality in children's educational outcomes (Mayer 2001, Owens ; Quillian ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research on the consequences of rising income inequality has focused on the economic segregation produced by more affluent residents sorting into different school districts than their less advantaged counterparts (Owens et al. ); these trends are particularly acute among parents (Owens ), which suggests that schooling considerations play a central role in parents’ residential choices. The growing economic segregation across school districts has contributed to rising inequality in children's educational outcomes (Mayer 2001, Owens ; Quillian ).…”
Section: Introductionmentioning
confidence: 99%
“…While some research has also considered economic sorting among schools within large districts (Owens et al. ), far less research has considered the educational dynamics within economically diverse school attendance zones, where neighborhood integration may produce integration within the local schools. The presence of alternatives to the local public schools may actually facilitate neighborhood socioeconomic integration: “[A]s options for non‐neighborhood public and private schools proliferate, families may feel more free to enact their ideal residential preferences without concern for school quality” (Goyette , p. 17).…”
Section: Introductionmentioning
confidence: 99%
“…1 Such anxieties and preferences could be magnified by playing out a time when residential segregation by income has been sharply increasing (Reardon and Bischoff, 2011), particularly among families with children (Owens, 2016) and with consequences for the income segregation of schools 1 Additionally, high-SES parents could increase their investments in children more strongly in reaction to rising income inequality than lower-SES parents because their investments of time and money in children are more effective (Guryan et al 2008;Hsin, 2009;Villena-Roldan and Rios-Aguillar, 2012) or because high-SES parents may be more informed about the benefits of such investment (Kalil et al, 2012). and districts (Owens, Reardon, and Jencks, 2016). High-SES parents are then increasingly surrounded by like-minded peers, which might intensify their motivation to invest in children (Blalock, 1984).…”
Section: Contextual Effects On Parental Preferencesmentioning
confidence: 99%
“…The 20% highest achieving students at a low-poverty schools will likely score very differently from the 20% highest achieving students at high-poverty schools but both will likely require additional educational opportunities outside the general classroom to prevent their academic achievement from plateauing (Callahan & Miller, 2005;Reis & Renzulli, 2010;Subotnik et al, 2011). As communities and schools become more economically segregated and larger proportions of students fall below the poverty line, steps need to be taken to help bolster disadvantaged students' probability of success (Owens, 2010;Owens, Reardon, & Jencks, 2016;Plucker & Peters, 2018). There have been many studies quantifying the unequal educational opportunities for children of different social classes and exploring how income gaps develop over time but few scholars that have put forth school-based local norms as a possible solution (McBee, 2010;Olszewski-Kubilius & Corwith, 2018;Peters & Engerrand, 2016;Plucker & Peters, 2018).…”
Section: The Current Studymentioning
confidence: 99%
“…As a result of the increasing social stratification of neighborhoods and the relatively small size of elementary schools, school quality (e.g. quality and number of teachers, curriculum) varies largely as a function of the financial resources of one's neighborhood, and students in the same school tend to have similar SES backgrounds (Entwisle & Alexander, 1999;Owens, 2010;Owens et al, 2016;Plucker & Peters, 2018). Using school locale as a proxy for neighborhood, the models in this study aim to examine the variability in proportion of identified gifted students between schools by altering the cut score using several norming procedures.…”
Section: The Current Studymentioning
confidence: 99%